2022
DOI: 10.32479/ijeep.11711
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization Using Electric Ground Support Equipment in Aviation Industry

Abstract: An airport is one of the country's infrastructures that provides air transportation services. In providing its services, To ensure aircraft safety, airports must conform to a set of international technical operating standards and planned operating procedures. In addition, airports also have a social responsibility to prevent pollution and support eco green. Therefore, this study aims to conduct a benefit cost analysis using electric ground support equipment in  aviation industry, both for using e-GSE using die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Aspek pengaturan parkir pesawat dan pengisian bahan bakar juga merupakan bagian penting dari ground handling, yang melibatkan perencanaan yang cermat untuk memaksimalkan efisiensi dan keamanan di area apron. Dengan memiliki standar operasional yang ketat dan tenaga kerja yang terlatih, ground handling berperan penting dalam menjaga keamanan, ketepatan waktu, dan kenyamanan dalam perjalanan udara bagi penumpang dan pihak terkait (Sari, 2022).…”
Section: Pendahuluanunclassified
“…Aspek pengaturan parkir pesawat dan pengisian bahan bakar juga merupakan bagian penting dari ground handling, yang melibatkan perencanaan yang cermat untuk memaksimalkan efisiensi dan keamanan di area apron. Dengan memiliki standar operasional yang ketat dan tenaga kerja yang terlatih, ground handling berperan penting dalam menjaga keamanan, ketepatan waktu, dan kenyamanan dalam perjalanan udara bagi penumpang dan pihak terkait (Sari, 2022).…”
Section: Pendahuluanunclassified
“…Ref. [42] analysed the benefits of adopting electric ground support equipment (EGSE) in the aerospace industry using a benefit-cost ratio approach. The cost of diesel-and electricity-powered EGSE was also evaluated in the study, and it was found that both options are financially feasible, with the diesel-powered EGSE having a longer usable life.…”
Section: Estimating Electric Ground Support Equipment Energy Demandmentioning
confidence: 99%
“…Flight ground support refers to the service process centered around passengers, cargo, and aircraft maintenance, which occurs between two key support points: when an aircraft arrives at its parking position and when it departs from it [1][2][3] [4]. With the gradual easing of the global pandemic and the gradual reopening of borders by various countries, air transportation volumes are steadily recovering and expected to continue growing smoothly.…”
Section: Introductionmentioning
confidence: 99%